Cidade de Nampula: a Rainha do Norte de Moçambique - Araújo, Manuel Mendes (2005)
The city of Nampula, located in the Northern hinterland of Mozambique, has always been considered the «capital of the North». Founded with the aim of ensuring military control over the colonial penetration of the hinterland, it is an important crossroads where the litoral-hinterland and centre-North axes intersect. Just like Mozambique’sother urban areas, the city of Nampula underwent considerable demographic growth in the period that followed the independence of the country, including the period of civil war and the peace that ensued from 1992 onwards. This demographic growth was the result of a significant migration inflow originating in the rural areas. As the city’s infrastructure and economic activity was unable to keep apace with this growth, the idea of migrating to the city with the aim of improving the livelihood of the migrant population was nothing but a mirage, which eventually resulted in the proliferation of the informal economy as a means of livelihood. The «city of concrete» still exhibits a series of urban and demographic haracteristics that differ substantially from those of the surrounding urban administrative units.